Implementation of learning into person-centred practice: evidence of impact from community nursing preparation programmes - Tyagi, Vaibhav; Churchill, Julie; Dickson, Caroline (Frontiers in Health Services, 2025)
IntroductionThere has been a global move towards personalising and “humanising” healthcare and promoting caring cultures. Education is addressing this agenda by incorporating person-centred principles into teaching and learning. The aim of this research was to explore the implementation of person-centred learning into healthcare practice. More specifically, this study aims to explore community nurses' implementation of learning about person-centredness in their practice and to demonstrate the impact of person-centred curriculum.MethodsA cross-sectional quantitative survey design was used with community nursing graduates and current students who engaged with person-centred curricula.ResultsSignificant improvements were found in three constructs of person-centred practice—clarity of beliefs and values, knowing self and developed interpersonal skills.DiscussionThese findings provide support for the development of pre-requisites of person-centred practice, rather than person-centred processes in pre-registration curricula. With key pre-requisites for person-centred practice such as leadership attributes of knowing self and of advanced communication skills, learners and graduates will be able adopt healthful leadership practices which are vital in developing others and in creating person-centred cultures.